IMPROVING THE QUALITY OF THE MATERIAL TRANSPORT PROCESS IN SEWING MACHINES - КОРОБЧЕНКО, ЄВГЕНІЙ; ГОРОБЕЦЬ, ВАСИЛЬ; КРИКУН, ЄВГЕНІЙ (Technologies and Engineering, 2024)
Purpose. Conduct an analysis of the impact of the structure and design parameters of material displacement mechanisms and their working elements on the operational performance quality of the sewing machine to identify areas for improvement. Methodology. A well-known method of analytical review of information sources dedicated to addressing the aforementioned issue has been applied. Findings. As a result of the research of literary sources, it was found that the operational performance of sewing machines, and thus the quality of their work in the material displacement mechanism, is influenced by the following factors: the material and mass of the presser foot, the physical and mechanical properties of its surface, and the parameters of the dynamic system "presser foot-material-transporting mechanism" (including the pressure force applied to the material against the throat plate during transport and the dimensions of the presser foot). The construction of the transporting mechanism, the shape and condition of its working surface, its motion law and trajectory, especially in the presence of several transporting mechanisms considering their compatibility, are also important. Despite various measures proposed to improve the machine’s operational performance, complete elimination of negative phenomena in the material transport process is not achieved. A radical improvement in the quality of material transport in sewing machines is possible only through the development of fundamentally new creative methods and means of transportation that can ensure equal conditions for moving the upper and lower layers of material. Originality. The scientific novelty of this research lies in revealing the essence of the impact of parameters (and their combinations) of transport mechanisms and their working elements on the quality of sewing products; in identifying the shortcomings of known processes and mechanisms for material transport in sewing machines; and in determining the main directions for improving the quality of their operational performance. Practical value. The results of the analysis can be used for the targeted development of new, more promising methods, devices, and mechanisms for material displacement in sewing machines.